What’s Behind the Bank Account? – Questions about Distinguishing Account Types - Milán Kiss (Financial and Economic Review)
The essay presents a classification of the types of accounts maintained by financial entities and their different legal definitions. The colloquial term “bank account” can in fact encompass a variety of account types, including payment, deposit, client or electronic money accounts, each of which is subject to distinct regulatory rationales and operating principles. The classification of accounts also determines the prudential measures applicable, the necessary authorisations, the requirements for IT systems and the responsibilities of service providers. The essay delineates the evolution of EU financial regulation, emphasising the significance of the Lamfalussy framework and the role of EU regulations in the development of the prevailing financial institutional system. Accurate accruals are of particular importance for financial sector actors. The type of account has a fundamental impact on the feasibility of the business model and regulatory compliance.